Tailoring nirvana: Appropriating yoga, resignification and instructional challenges. (1st September 2016) - Antony, Mary Grace
As an appropriated cultural artefact, yoga provides the opportunity to examine how resignification alters instructional goals and outcomes. This project critically examines instructional challenges experienced by non-Indian yoga teachers, with an emphasis on how resolving these issues impacts pedagogical relationships. Findings demonstrate that student preferences require instructors to resignify yoga instruction within three areas: replacing Sanskrit nomenclature with more relatable terminology; highlighting the physiological (rather than religio-spiritual) benefits; and varying asana routines to discourage boredom. Together, these themes overlap and reinforce one another to ideologically rearticulate yoga as fitness and physical therapy, and thus discursively shift the focus of yoga practice from text/artefact (yoga) to consumer (student).